Group 10–group 14 metal complexes [E–TM]IV: the role of the group 14 site as an L, X and Z-type ligand. Issue 36 (18th August 2016) - Wächtler, Erik; Gericke, Robert; Brendler, Erica; Gerke, Birgit; Langer, Thorsten; Pöttgen, Rainer; Zhechkov, Lyuben; Heine, Thomas; Wagler, Jörg
Abstract : The group 14 element's ligand role in N, S-bridged transition metal complexes was shown to depend on both atoms' substitution patterns. Abstract : A series of new complexes of a general motif [R2 E(μ-N, S)2 TM–L] (E: metalloid group 14 element; TM: group 10 metal; R: Cl, Ph, pyS, OH, (N, N, O)-chelating ligands; N, S: 1-methylimidazole-2-thiolate (methimazolyl, mt − ), pyridine-2-thiolate (pyS − ); L: PPh3, PCy3, pyS) was synthesised and characterised by single-crystal X-ray diffraction, multi-nuclear NMR spectroscopy ( 1 H, 13 C, 31 P, 119 Sn), 119 Sn Mössbauer spectroscopy and quantum chemical calculations. The E–TM bonding situation in these compounds can be described with various resonance structures which comprise E(ii )→TM(ii ), E(iii )–TM(i ) and E(iv )←TM(0) features. Thus, in these complexes the atoms of the group 14 based ligand sites reveal L-, X- and Z-type ligand characteristics. A systematic comparison between structural and spectroscopic parameters as well as the results from NLMO analyses of structurally related compounds provided information about the differences in the E–TM bonding situation upon alteration of the metal atoms or ligand patterns. Under investigation are the structurally related compounds [Cl2 Sn(μ-pyS)2 TM–PPh3 ] (1 : TM = Pd;2 : TM = Ni;3 : TM = Pt), [Cl2 Ge(μ-pyS)2 Pd–PPh3 ] (4 ) and, for in silico analysis, [Cl2 Si(μ-pyS)2 Pd–PPh3 ] (5 ), which indicate a pronounced shift of the E–TM bond electron pair towards TM for TM = Pt. Further complexes serve as representatives of these compounds with different bridging ligands [Cl2 Sn(μ-mt)2 Pd–PPh3 ] (8 ), different trans -E–TM-bound ligands [Cl2 Sn(μ-pyS)2 Pd–PCy3 ] (9 ), [Cl2 Sn(μ-pyS)2 Pd]4 (10 ) and with different substituents at Sn (including penta- and hexacoordinated tin compounds), i.e., [R2 Sn(μ-pyS)2 Pd–PPh3 ] with R = Ph (6 ) and pyS (7 ), [(O, N, N)Sn(μ-pyS)2 Pd–PPh3 ] (11 ) and (12 ) having two different (O, N, N) tridentate ligands, and [(μ-OH)ClSn(μ-pyS)2 Pd–PPh3 ]2 (13 ). The latter series indicates a shift of the E–TM (= Sn–Pd) bond electron pair towards Pd upon transition from penta- to hexacoordinated tin compounds.